Electricity saving receipt as electricity consumption efficiency innovation using behavioral economic science approach - Prima Gandhi; Aceng Hidayat (Monas: Jurnal Inovasi Aparatur, 2022)
The demand for electrical energy in Indonesia continues to increase in line with the increase of population. The government through PT. PLN continues to increase the production of electrical energy using fossil energy sources. As a result of diminishing fossil energy sources, the government expects public participation to maintain the sustainability of the electrical energy supply by performing efficient use of electricity. One of the efforts that can be made and the goal of this research is to practice the innovation of electricity-saving receipts. The electricity-saving receipt innovation is an innovation that combines the concepts of behavioral economics, efficiency, self-control, and sustainable development. This innovation seeks to make the public know and be able to compare the electricity consumption of their household with those of nearby households. This research was performed using experimental method and the first conducted in Indonesia. The research design used is Pre-Experimental Design with the one-group pre-test and post-test design model. This research was conducted in Cihideung Udik Village, Ciampea District, Bogor Regency. Bogor Regency from March to July 2021. The choice of research location was done purposively. This study used primary and secondary data from PT. PLN. The result of this research is related to the knowledge of electricity subsidies with an increase of 45%. Likewise with the 3M movement (Turn Off, Unplug, and Set) shows an increase of 80%. Regarding the average use of electrical energy per KWH, it was decreased by 32 KWH for 900 VA power users and 34 KWH for 450 VA power users. The innovation of electricity-saving receipts is the realization of the 7th SDGs goal.